The world we knew [videorecording (Blu-Ray)] - Jones, W. W.; Lake, Kirk; Lake, Kirk; Myers, Johann; Rodger, Struan; Lynch, Finbar (BayView Entertainment, 2026)
After a job goes wrong, six armed robbers must spend a single night at a deserted safe house. But during their stay their pasts come back to haunt them. What is real and what is the product of their tormented minds?